High SHIP2 Expression Indicates Poor Survival in Colorectal Cancer. (24th November 2014) - Yang, Ju; Fu, Maoying; Ding, Yaoguang; Weng, Yajing; Fan, Weifei; Pu, Xiaolin; Ge, Zhijun; Zhan, Feng; Ni, Huihui; Zhang, Wei; Jin, Feng; Xu, Ning; et al.
Abstract : SH2-containing inositol 5′-phosphatase 2 (SHIP2), which generally regulates insulin signaling, cytoskeleton remodeling, and receptor endocytosis, has been suggested to play a significant role in tumor development and progression. However, the associations between SHIP2 expression and the clinical features to evaluate its clinicopathologic significance in colorectal cancer (CRC) have not been determined yet. In the present study, one-step quantitative real-time polymerase chain reaction (qPCR) test and immunohistochemistry (IHC) analysis with CRC tissue microarrays (TMA) were employed to evaluate the mRNA and protein expression of SHIP2 in CRC. The results showed that SHIP2 expression in the mRNA and protein levels was significantly higher in CRC tissues than that in corresponding noncancerous tissues (both P < 0.05 ). The expression of SHIP2 protein in CRC was related to lymph node metastasis ( P = 0.036 ), distant metastasis ( P = 0.001 ), and overall survival ( P = 0.009 ) . Kaplan-Meier method and Cox multifactor analysis suggested that high SHIP2 protein level ( P = 0.040 ) and positive distant metastasis ( P = 0.048 ) were critically associated with the unfavorable survival of CRC patients. The findings suggested that SHIP2 may be identified as a useful prognostic marker in CRC and targeting CRC may provide novel strategy for CRC treatment.